A new magnetic tailor made polymer for separation and trace determination of cadmium ions by flame atomic absorption spectrophotometry. Issue 105 (31st October 2016) - Zarezade, Vahid; Behbahani, Mohammad; Omidi, Fariborz; Abandansari, Hamid Sadeghi; Hesam, Ghasem
Abstract : Magnetic ion imprinted polymers have been prepared and applied for the selective extraction and trace monitoring of cadmium ions in food samples. Abstract : Magnetic ion imprinted polymers have been prepared and applied for the selective extraction and trace monitoring of cadmium ions in food samples. The characterization of synthesized sorbent was carried out by Fourier transform infrared spectroscopy, elemental analysis, scanning electron microscopy, X-ray diffraction, and thermal analysis. The separation of magnetic nanoparticles from the extraction solution could be easily carried out by applying an external magnetic field. Flame atomic absorption spectrophotometry was used for determination of the extracted target ion. The detection limit and linear dynamic range for the coupling of the proposed sample preparation method under the optimized conditions with FAAS were 0.02 μg L −1 (based on 3 S b / m ) and 0.1–500 μg L −1, respectively. Finally, the applicability of the coupling of the solid phase extraction method with flame atomic absorption spectrophotometry was investigated by extraction and monitoring of cadmium ions in food samples. Therefore, the introduced technique can be applied by food scientists as a reliable pre-concentration stage before determination of cadmium by flame atomic absorption spectrophotometry.